Automation System for Kiosk Ordering Processes for Tourists - Nazarov F.; Salimova M. (Research Parks Publishers, 2024)
In this research work, the system of automating kiosk ordering processes for tourists and its possibilities are mentioned. In this, the service functions of kiosks, better and faster customer service, adequate satisfaction of customer needs, prevention of disagreements between customers and employees, ordering kiosks for tourists and their capabilities are fully covered.